Systemic risk and Efficiency analysis of the banking sector: A comparative study of Indian Public and Private Banks - Chhabra, Khushdil; Soni , Pooja; Gill, Suveera (Gyan Management Journal, 2023)
The academics, policymakers and regulators have shown significant  curiosity in the study of systemic risk. Intra-country systemic risk has  been studied in context of developed economies, but in the context  of developing economies it seems to be rare. This research paper’s  objective is to present an innovative presentation of the complex  interplay between efficiency and systemic risk in Indian banking  sector- public and private banks. Due to disagreement among the  scholars regarding the relationship between these two factors, we tried  to investigate this issue by collecting data from banks listed on the  Nifty PSU Bank Index and Nifty Private Bank Index over the period  from 2003-04 to 2018-19. The fundamental connection between  efficiency and systemic risk has been checked threw granger causality.  The results indicate that efficiency and systemic risk are significantly  and negatively related, and the relationship is bi-directional for  private banks and uni-directional for public banks. Both scholars and  regulators could benefit from this article findings.
Keywords: Systemic risk; Efficiency; Banking Sector; Contagious; GFC